Correction: Biathletes present repeating patterns of postural control to maintain their balance while shooting. - Justyna Michalska; Rafał Zając; Krzysztof Szydło; Dagmara Gerasimuk; Kajetan J Słomka; Grzegorz Juras (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0267105.].